The management of oroantral communication post dentral extraction M1: a case report - Sulfiana, Sulfiana; Riawan, Lucky; Priyanto, Winarno (Journal of Case Reports in Dental Medicine, 2019)
Objective : The purpose of this to report the management of oronatral communication case after extraction of first upper molar.Â Method : A 45 y.o male patient came with discharge from the nose after tooth extraction, 3 hours prior to admission when he was extraction right upper tooth. Ginggival hyperemis of tooth 16 region. The therapy we performed was upper right molar buccal flap and analgesics and rhinoceros.ResultsÂ : At the time of discharge the hospital was given rhinos caps 3x125 mg and medication from the previous hospital continued. Patient had no complaints when control back. Healing wounds in the flap shows good healing. And the patient no longer complains that there is fluid leakage while garglingConclussion : In this case, OAC cosure was treated with buccal flap and was given medication. The improvement was noted